The effectiveness of the self-questioning strategy in acquiring historical concepts (Journal of the College of Basic Education, 2022)
This research aims to identify (the effectiveness of the self-questioning strategy in acquiring historical concepts).The researcher randomly selected Samarra First High School for Boys affiliated to the Samarra Education Department / General Directorate of Salahuddin Education to implement the experiment and selected his sample in the same way. And the control group, the number of its students (28) students, represented by Division (B), and the subject of Arab and Islamic history is taught according to the usual method. intelligence).